Incidence of Salmonella spp., Klebsiella spp., Proteus spp. and Two Micronutrients (Zinc and Iron) Present in Poultry Feeds Collected from Sokoto, Nigeria - Nura Maiakwai Salah; Asiya Gidado Yabo; AI Umar; Yusuf Sarkingobir; Atiku Yari Dogon Daji; Rilwanu Umar (International Journal of Pollution: Prevention & Control, 2023)
Mostly, poultry quality is determined by its feed. Thus, in this time of ravaging pollution and infectious diseases monitoring of quality of products related to poultry is eminent. This study aimed at determining the incidence of some microbes and micronutrients (zinc and iron) in poultry feed in Sokoto, Nigeria. Standard methods and materials of analytical grade were used. Zinc and iron micronutrients were determined in feed and egg using atomic absorption spectroscopy. Likewise, standard methods were used to determine Salmonella spp., Klebsiella spp. and Proteus spp. in feed. The most frequent bacteria were Salmonella spp., then Klebsiella, and lastly the Proeus spp. The concentrations of zinc and iron micronutrients present in different poultry feeds and whole egg are as follows: the zinc values in different feeds range from 10.12 ± 3.5 to 20.60 ± 6.6 ppm; and the iron values range from 14.6 ± 0.12 to 40.10 ± 2.5 ppm (P < 0.05). The chronic daily index for zinc and iron are lower than 1, the hazard quotient for zinc is very elevated, and that of iron is lower than 1. However, the hazard index values for the micronutrients is of concern, because they are above 1. The found organisms may contaminate poultry products and adversely affect the public health. However, the micronutrients determined in different feeds were lower than standard, but the presence of these metals in the examined poultry egg could pose hazard to the public like the microbes.
Keywords: Microbes; Poultry; Zinc; gg; hazard; iron; micronutrient